A Review on Phase Change Materials Incorporation in Asphalt Pavement - Intan Kumalasari; Madzlan Napiah; Muslich H. Sutanto (Indonesian Journal of Science and Technology, 2018)
Phase Change Material (later to be referred as PCM) has been successfully utilized in some areas. PCM has emerged as one of the materials for pavement temperature reducing due to its latent heat. Some research has been done regarding this topic. The objective of this paper is to review the development of PCM in asphalt pavement. The review has shown that organic PCM appears as the favourite PCM in asphalt concrete studies. Choice of porous material depends on method of incorporation. Reduction of temperature in PCM-asphalt mixture compared to conventional one is undoubtable. However, the mechanical performance of PCM-asphalt mixture need to be explored.